2005
DOI: 10.1088/0022-3727/38/13/005
|View full text |Cite
|
Sign up to set email alerts
|

High-speed quantum dot lasers

Abstract: The modulation bandwidth of conventional 1.0-1.3 µm self-organized In(Ga)As quantum dot (QD) lasers is limited to ∼6-8 GHz due to hot carrier effects arising from the predominant occupation of wetting layer/barrier states by the electrons injected into the active region at room temperature. Thermal broadening of holes in the valence band of QDs also limits the performance of the lasers. Tunnel injection and p-doping have been proposed as solutions to these problems. In this paper, we describe high-performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
90
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(94 citation statements)
references
References 29 publications
4
90
0
Order By: Relevance
“…[11][12][13] Vice versa, in the p-doped device, the built-in hole reservoir allows fast hole-hole scattering to occur even at low electrical injection corresponding to electrons occupying only the GS. In this case, after the removal of a GS electron-hole pair by the pump pulse, electrons recover with 4 , while holes are characterized by the ultrafast recovery times 1 , 0 , which explains the well separate time constants of the gain dynamics for the p-doped case in Fig. 2.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…[11][12][13] Vice versa, in the p-doped device, the built-in hole reservoir allows fast hole-hole scattering to occur even at low electrical injection corresponding to electrons occupying only the GS. In this case, after the removal of a GS electron-hole pair by the pump pulse, electrons recover with 4 , while holes are characterized by the ultrafast recovery times 1 , 0 , which explains the well separate time constants of the gain dynamics for the p-doped case in Fig. 2.…”
mentioning
confidence: 78%
“…InAs/GaAs QD lasers incorporating p-doping were shown to exhibit temperature insensitive threshold current 1 and linewidth enhancement factor, 2 high peak modal gain, 3 and high modulation bandwidth. 4 The effect of p-doping in accelerating the carrier dynamics for application of QD lasers and amplifiers in high-speed communication has been particularly debated. In previous works, 5,6 we demonstrated that complete gain recovery can be achieved after few picoseconds in InAs QD amplifiers at high level of electrical injection at room temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This frequency can be enhanced by increasing the pump power. This technique was used to demonstrate small-signal modulation rates of several tens of gigahertz, 13 but relatively large pump powers were necessary, making these lasers impractical for low-power applications. Our approach has been to use the large purcell enhancement and hew·c large (J factors to increase the modulation rateY \Ve fabricated InAs quantum dot photonic crystal lasers in GaAs membranes (see structure in Fig.l(c)).…”
Section: Quantum Dot Protonic Crystal Lasersmentioning
confidence: 99%
“…Semiconductor diode lasers incorporating self-assembled quantum dots (QDs) on GaAs substrates accessing the International Telecommunication Union (ITU) O-band (1.26-1.36 lm) have received considerable attention, to the point of their current commercialization, 1,2 with recent performance milestones reached including high-speed, temperature-insensitive 3 operation around room temperature (RT) at 1.3 lm through the use of p-type doping. 4 In contrast to quantum well lasers, the modulation dynamics of QD lasers are limited by damping, 5 and in order to achieve high modulation rates, low carrier scattering times into the lasing state and high saturated modal gains are required. Possible routes to increase saturated gain include careful optimization of growth conditions to increase QD areal density 6 or to increase differential gain by increasing p-doping, but this has practical limit in terms of additional loss.…”
mentioning
confidence: 99%